A huge benign ovarian mucinous cystadenoma in post-menopausal woman - Verma, Kamala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Mucinous cystadenomas are the second most common type of epithelial tumor of ovary. Most of these tumors are benign. However some tumor can grow to enormous size. In modern world giant benign tumor of ovary are rare because of improved diagnostic technologies and general awareness of public. This report presents the case of 50 year old post-menopausal, grand multiparous woman having a very large mucinous cystadenoma. She had laparotomy followed by total hysterectomy with bilateral salpingo- oophorectomy. Her post-operative course was uneventful. She came for follow up in healthy condition.